ความท้าทายรูปแบบใหม่และวาทกรรรมการพัฒนา: ผลกระทบต่อทิศทางนโยบายสังคมของประเทศไทย - สว่างศิลป์ สรสิช; Evans, Gwyn Peredur (วารสารสังคมสงเคราะห์ศาสตร์และการบริหารสังคม, 2021)
This paper seeks to explain Thailand’s social policy shift in response to the immediate challenge of COVID-19 by investigating the role of development discourses of human rights, human security and sustainable development both at the global and domestic levels, and their interaction to, and influence on key actors of the particular context of the COVID-19 pandemic. The paper argues that social policy formation and shift is not only determined by this immediate phenomenon itself but also through the development discourses that create international norms, order, and practice. With discursive analysis, this article opens a new space for further discussion on social policy formation and change in Thailand.